Elementi menjave daru v tržni ekonomiji - Rus, Andrej (Družboslovne razprave, 2010)
The purpose of this analysis is to examine whether a market exchange is really an exchange of alienated, impersonal and anonymous objects, devoid of moral and social elements or obligations, and therefore strictly distinct from gift exchange, as presupposed by the dichotomous socio-anthropological model of exchange. Marketing practices have changed significantly in the past few decades and sometimes contain elements which imitate a gift exchange. Analysis shows that contemporary marketing techniques often decommoditise market exchanges: they build long-term relationships between a company and its customers, create moral obligations, reduce alienation and enable a transfer of identities, thereby infusing the features of a gift exchange into a market exchange.
Keywords: Social anthropology; Socialna antropologija; Tržno gospodarstvo; Market economy; Blagovna menjava; Commodity exchange; marketing